Plasma cell‐free DNA quantification is highly correlated to tumor burden in children with neuroblastoma. (14th June 2018) - Wang, Xisi; Wang, Lijun; Su, Yan; Yue, Zhixia; Xing, Tianyu; Zhao, Wen; Zhao, Qian; Duan, Chao; Huang, Cheng; Zhang, Dawei; Jin, Mei; Cheng, Xianfeng; et al.
Abstract: To evaluate plasma cell‐free DNA (cfDNA) as a promising biomarker for neuroblastoma (NB) tumor burden. Seventy‐nine eligible patients with newly diagnosed NB were recruited from Beijing Children's Hospital between April 2016 and April 2017. Additionally, from September 2011 to June 2017, 79 patients with stable NB were evaluated with a median follow‐up time of 21 months. Approximately 2 mL of peripheral blood was drawn upon enrollment, and plasma cfDNA levels were measured via quantitative polymerase chain reaction (qPCR). Total cfDNA analysis was performed using the long interspersed nuclear element 1 (LINE‐1) 79 bp fragment, and DNA integrity was calculated by the ratio of the LINE‐1 300 bp fragment to the LINE‐1 79 bp fragment. A total of 79 NB patients with a median age of 36 months comprised the group of newly diagnosed NB patients. The main primary tumor site was the retroperitoneal and adrenal region (81%). Three or more metastatic sites were found in 17.7% of patients. Stable NB patients older than 18 months comprised 98.7% of the stable NB patients. Neuron‐specific enolase (NSE), lactate dehydrogenase (LDH), and cfDNA levels were dramatically increased in the newly diagnosed NB patients and significantly different from those in the stable NB patients. Moreover, the concentration of cfDNA was much higher in patients with larger tumors. By analyzing the area under the receiver operator characteristic (ROC) curve (AUC), the areas of total cfDNA, NSE, and LDH levels were 0.953, 0.929, and 0.906, respectively. The sensitivity and specificity data clarified that the level of circulating cfDNA in plasma can be considered as a reliable biomarker for describing tumor load in NB. The plasma cfDNA concentration was as good as the levels of LDH and NSE to discriminate the tumor burden in children with NB. Abstract : The concentration of plasma cell‐free DNA is significantly upregulated in newly diagnosed NB patients compared with stable NB. Consistent with the pattern of serum tumor markers in NB, plasma cell‐free DNA is significantly higher in high‐risk NB than low‐risk NB. Plasma cell‐free DNA can be served to detect minimal residual disease of NB and closely correlates to tumor burden.